Cross phase polarization algorithm for fault direction determination using zero crossing method to determine phase difference - Abidin A.A.B.Z.; Ramasamy A.; Abidin I.Z.; Nagi F.H. (2023)
Power systems are usually connected in a condition where there is more than one power supply or voltage source supplying a load. These systems will have protection relays to protect various equipment connected to the system. However in isolating a fault, the direction of the fault needs to be known in order to limit the amount of loss load. This paper shall describe a possible algorithm that could be used in order to perform cross phase polarization. The possible faults that could be detected using this technique include the single phase to ground fault, the phase to phase fault and the double phase to ground fault. Three phase faults require the memory polarization technique that will not be discussed in this paper. The algorithm shall be implemented and tested using the sim power system tool box present in MATLAB. 2009 IEEE.